Evaluation of silicon strip detectors in transmission mode for online beam monitoring in microbeam radiation therapy at the Australian Synchrotron. (12th December 2021) - Davis, Jeremy; Dipuglia, Andrew; Cameron, Matthew; Paino, Jason; Cullen, Ashley; Guatelli, Susanna; Petasecca, Marco; Rosenfeld, Anatoly; Lerch, Michael
Abstract : This study provides an extensive evaluation of the suitability of transmission detectors for use in synchrotron‐based microbeam radiation therapy applications. Abstract : Successful transition of synchrotron‐based microbeam radiation therapy (MRT) from pre‐clinical animal studies to human trials is dependent upon ensuring that there are sufficient and adequate measures in place for quality assurance purposes. Transmission detectors provide researchers and clinicians with a real‐time quality assurance and beam‐monitoring instrument to ensure safe and accurate dose delivery. In this work, the effect of transmission detectors of different thicknesses (10 and 375 µm) upon the photon energy spectra and dose deposition of spatially fractionated synchrotron radiation is quantified experimentally and by means of a dedicated Geant4 simulation study. The simulation and experimental results confirm that the presence of the 375 µm thick transmission detector results in an approximately 1–6% decrease in broad‐beam and microbeam peak dose. The capability to account for the reduction in dose and change to the peak‐to‐valley dose ratio justifies the use of transmission detectors as thick as 375 µm in MRT provided that treatment planning systems are able to account for their presence. The simulation and experimental results confirm that the presence of the 10 µm thick transmission detector shows a negligible impact (<0.5%) on the photon energy spectra, dose delivery and microbeam structure for both broad‐beam and microbeam cases. Whilst the use of 375 µm thick detectors would certainly be appropriate, based upon the idea of best practice the authors recommend that 10 µm thick transmission detectors of this sort be utilized as a real‐time quality assurance and beam‐monitoring tool during MRT.